Dialog peradaban dan pertembungan peradaban : kajian perbandingan - Mohamad Zaidin Mat Mohamad; Kamal Mujani, Wan; Ermy Azziaty Rozali (Dewan Bahasa dan Pustaka, 2016)
On comparative study in the dialogue of civilizations and clash of civilizations.